Performance Analysis of ECS Architecture in 2D Mobile Game Development: Ocean Hero - Raynaldi Irfansya Regar; Benny Pinontoan; Christian A. J. Soewoeh (PT. Tech Cart Press, 2026)
Mobile game development frequently encounters computational performance bottlenecks when a system must render and update the logic of many objects simultaneously in each frame. Conventional Object-Oriented Programming (OOP) architecture produces high memory overhead and elevated cache miss rates because game objects are allocated in scattered, non-contiguous memory locations. This research aims to design, implement, and analyze the performance of an Entity Component System (ECS) architecture in a 2D Android educational arcade game titled Ocean Hero. The development process followed the Game Development Life Cycle (GDLC). ECS separates identity, data, and behavior into entities, components, and systems, allowing game logic to process homogeneous component data sequentially through Unity DOTS. Evaluation was conducted on a Samsung Galaxy A15 4G by comparing ECS and OOP implementations through white-box functional verification and stress testing across six entity workloads from 500 to 3,000 entities, each observed over a 20-second tracking period. The ECS implementation maintained a stable 30 FPS and 33.3 ms frame time across all tested entity levels. In contrast, the OOP implementation degraded to 11 FPS and 90.73 ms frame time at 3,000 entities. Based on the relative performance improvement formula, ECS achieved approximately 172.7% higher runtime performance than OOP at the highest workload. These results confirm that ECS is an effective architectural solution for improving scalability and computational efficiency in real-time 2D mobile games with large entity counts.